PENYIDIKAN TINDAK PIDANA NARKOTIKA DI INDONESIA - Triadi Triadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Narcotics are substances or drugs derived from plants or non-plants, both synthetic and semisynthetic, which can cause a decrease or change in consciousness, loss of taste, reduce to eliminate pain, and can cause dependence, which are divided into groups as follows: attached in Law no. 35 of 2009 concerning Narcotics. Drug abuse (narcotics and dangerous drugs) is an international crime and an extra ordinary crime (extraordinary crime). This extraordinary crime is a crime that has a systematic impact on people's lives. The process of investigating the problem of narcotics crime is a method of investigation or a system used to find and collect evidence in order to find the suspect and determine related criminal acts that occurred in accordance with the Criminal Procedure Code. After the investigative action, the criminal justice system switches to investigative action in accordance with the mandate of Law Number 35 of 2009 concerning Narcotics. The legal politics of investigation in Law Number 35 of 2009 concerning Narcotics can be seen from the scope of criminal law which includes three provisions, namely criminal acts, liability, and sentencing. In the process of drafting this Narcotics Law, there is a legal policy policy from legislation which mandates four categorizations of unlawful acts that are prohibited by law and can be threatened with criminal sanctions.